2020
DOI: 10.37358/rc.20.10.8346
|View full text |Cite
|
Sign up to set email alerts
|

New Bioactive Co(II) and Ni(II) Complexes with Ofloxacin Mixed-Ligand

Abstract: Four mixed-ligand metal(II) complexes with the molecular formulae [M(ofl)(bipy)]NO3�H2O and [M(ofl)(phen)]NO3�H2O were synthesized by the reaction of Co(II) and Ni(II) with ofloxacin (Hofl) in the presence of 1,10-phenanthroline (phen) / 2,2`-bipyridine (bipy) (1:1:1 molar ratio). The data obtained from elemental analysis, molar conductance, spectral infrared, reflectance spectra and magnetic studies gave information about the coordination of the ligands and the geometry of the metallic ion. The results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This may yield new probable binding conformations between the bioactive compounds and the biological active target on the receptor. Furthermore, understanding the structure generates new information that helps comprehend how the physiological response is obtained [14].…”
Section: Introductionmentioning
confidence: 99%
“…This may yield new probable binding conformations between the bioactive compounds and the biological active target on the receptor. Furthermore, understanding the structure generates new information that helps comprehend how the physiological response is obtained [14].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the binding behaviour of bisphosphonates to PDA plays an important role in elucidating the fundamental biochemical processes in which these compounds participate. Currently, the results reported in the specialized literature [8,21] have indicated that the approach of ligand-biological receptor binding design (molecular docking studies and structure-activity/property correlation techniques) allows the exploration of probable binding conformations of biologically active compounds at the sites of the target protein. Furthermore, it provides useful information in understanding their structural and physico-chemical characteristics and, implicitly, in understanding their therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%